HUBUNGAN ANTARA INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KOMUNIKASI INTERPERSONAL SISWA SMAN 1 DEPOK SLEMAN D.I YOGYAKARTA - Umu Nisa Ristiana (Transformatif, 2018)
Abstract: This study aims to determine the relationship between intensity of using social media with interpersonal communication. The initial hypothesis of this study is that there is a positive significant relationship between the intensity of using social media with interpersonal communication. The population in this study amounted to 474 students. The sample selection using stratified random sampling with proportional allocation method and the result of class X 33 students, class XI 33 students and class XII 34 students. Data collection use scale, interview, and documentation. Method of data analysis using prerequisite analysis test (normality test and linierity test) and hypothesis test using pearson’s product moment correlation. Based on the results obtained statistical calculation of corrrelation coefficient (rxy) = 0.057 with p = 0.574 ( p> 0.05), the concluded of this study there is no relationship positive significant between the intensity of using social media with interpersonal communication of students SMAN 1 Depok Sleman D.I Yogyakarta.Keyword: Interpersonal Communication, Intensity Of Using Social MediaAbstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas penggunaan media sosial dengan komunikasi interpersonal. Hipotesis awal penelitian ini adalah terdapat hubungan positif yang signifikan antara intensitas penggunaan media sosial dengan komunikasi interpersonal. Populasi dalam penelitian ini berjumlah 474 siswa. Pemilihan sampel menggunakan teknik Stratified Random Sampling metode alokasi proporsional dengan hasil kelas X 33 siswa, kelas XI 33 siswa dan kelas XII 34 siswa. Alat pengumpulan data menggunakan skala, wawancara dan dokumentasi. Metode analisis data menggunakan pengujian prasyarat analisis (uji normalitas dan uji linieritas) dan uji hipotesis menggunakan Pearson’s Product Moment Correlation. Berdasarkan hasil perhitungan statistik didapatkan perolehan koefisien korelasi (rxy) = 0.057 dengan p = 0.574 ( p > 0.05 ), artinya tidak ada hubungan positif signifikan antara intensitas penggunaan media sosial dengan komunikasi interpersonal siswa SMAN 1 Depok Sleman D.I Yogyakarta.